Participatory knowledge integration to promote safe pesticide use in Uganda. Issue 128 (February 2022) - Wiedemann, Ruth; Stamm, Christian; Staudacher, Philipp
Abstract: Wicked problems exceed traditional sectoral and jurisdictional boundaries and involve multiple actors as stakeholders, victims, and culprits. Wicked problems inherently feature uncertainty and knowledge gaps. Science plays a crucial role in generating evidence for solving these problems and contributing to societal transformation. However, researchers may perceive and study problems detached from practitioners' perceptions of the world. We use the example of smallholder pesticide management in Uganda and the three types of knowledge approach, a framework borrowed from transdisciplinary research, to disentangle knowledge gaps. To identify these gaps, we integrated and co-produce knowledge in a two-day participatory workshop applying design thinking. Our results show, that a transition towards safe pesticide management depends on changes in the system, such as a revision and implementation of exiting regulation or professionalization of agro-dealers. Furthermore, this transition is only possible if interventions address target groups beyond the individual farmers (e.g. agro-dealers or district government officials). Compared to existing academic knowledge, co-produced knowledge provides a broader systemic perspective and yields more fine grained insights about potential new pathways. This investigation confirms, that practitioners' knowledge is more fine-grained and detailed, thus exemplifying how knowledge integration is essential to avoid a gap between what researchers investigate and what practitioners need. Highlights: Wicked problems are better understood through participatory integration of academic and non-academic knowledge. Design thinking is an innovative, human-centered approach to facilitate such a co-production of knowledge Co-produced knowledge unveils aspects of smallholder pesticide management that are not covered in present academic literature A participatory approach yields successful knowledge exchange, even when used at the dissemination phase of research